CCL2/CCR2 Axis Promotes the Progression of Salivary Adenoid Cystic Carcinoma via Recruiting and Reprogramming the Tumor-Associated Macrophages - Yang, Zihui; Li, Huan; Wang, Weiqi; Zhang, Jianying; Jia, Sen; Wang, Jun; Wei, Jianhua; Lei, Delin; Hu, Kaijin; Yang, Xinjie (Frontiers in Oncology, 2019)
Objective: The present study investigated the roles and underlying mechanism of CCL2/CCR2 axis in the interactions between tumor cells and tumor-associated macrophages (TAMs) during the progression of salivary adenoid cystic carcinoma (SACC). Methods: Immunohistochemical staining and survival analysis were performed to study the correlation and clinical value of CD68, CCL2, and CCR2 expression in SACC cases. CCL2 silencing by RNA interference and CCR2 blocking by CCR2 specific antagonist (RS504393) were performed. ELISA, qRT-PCR, western blot, immunofluorescence, flow cytometry, CCK8, scratch wound healing, and transwell assays were used to explore the functional roles and possible mechanism of CCL2/CCR2 axis in the interactions between SACC cells and TAMs. The effects of targeting TAMs by blocking the CCL2/CCR2 axis were investigated in a xenograft mice model with SACC cells. Results: The high infiltration of TAMs marked by CD68 was significantly correlated with the expression of CCL2 and CCR2 in SACC tissues. Notably, the high infiltration of TAMs and the overexpression of CCL2 were obviously associated with the clinical progression and poor prognosis of SACC. SACC cells derived CCL2 could activate its receptor CCR2 expression in TAMs in vitro. The in vitro results further indicated that the SACC cells derived CCL2 was involved in the recruitment, M2 polarization, and GDNF expression of TAMs through the CCL2/CCR2 axis. Meanwhile, TAMs derived GDNF promoted the proliferation, migration, and invasion of SACC cells through the GDNF/p-RET pathway. Treating immunodeficient mice with the CCR2 antagonist (RS504393) greatly inhibited the infiltration of TAMs and the tumorigenicity of SACC cells. Conclusion: These new findings indicated that the CCL2/CCR2 axis promoted the progression of SACC cells via recruiting and reprogramming TAMs. Targeting TAMs by blocking the CCL2/CCR2 axis might be a prospective strategy for SACC therapy.